Coating with Autologous Plasma Improves Biocompatibility of Mesh Grafts In Vitro: Development Stage of a Surgical Innovation. (17th September 2013) - Gerullis, Holger; Georgas, Evangelos; Eimer, Christoph; Arndt, Christian; Barski, Dimitri; Lammers, Bernhard; Klosterhalfen, Bernd; Borós, Mihaly; Otto, Thomas
Abstract : Purpose . To investigate mesh coating modalities with autologous blood components in a recently developed in vitro test system for biocompatibility assessment of alloplastic materials. Materials and Methods . Seven different mesh types, currently used in various indications, were randomly investigated. Meshes were coated prior to cultivation with autologous peripheral blood mononuclear cells (PBMCs), platelets, and blood plasma. Pretreated meshes were incubated over 6 weeks in a minced tissue assay, representative for fibroblasts, muscle cells, and endothelial cells originating from 10 different patients. Adherence of those tissues on the meshes was microscopically investigated and semiquantitatively assessed using a previously described scoring system. Results . Coating with peripheral blood mononuclear cells did not affect the adherence score, whereas coating with platelets and blood plasma increased the score suggesting improved biocompatibility in vitro . The previous ranking of native meshes remained consistent after coating. Conclusion . Plasma coating of meshes improves their biocompatibility score in a novel in vitro test system.